PENGARUH PROMOSI PENJUALAN, PERIKLANAN DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PADA PT. GREAT MATARAM CABANG SURAKARTA - Ariyani, Rosy; Trisnowati, Juni (Universitas Of Surakarta, 2022)
The purpose of this study was to determine the effect of sales promotion, advertising and personal selling on purchasing decisions at PT Great Mataram Surakarta. The population in this study were consumers of PT Great Mataram Surakarta which consisted of a pharmacy and a hospital with a total of 2219. The sampling method used was purposive sample with a total of 100 respondents. Data collection techniques using interviews and questionnaires. The data analysis technique used the t test, F test, multiple linear regression analysis and the coefficient of determination. The results of the data analysis technique using the t test obtained a value of 4.199, which means that it has a significant effect on purchasing decisions. The results of the data analysis technique using the F test obtained a value of 34.625, which means a simultaneous significant effect on purchasing decisions. The results of the data analysis technique using the coefficient of determination obtained a value of 0.505, which means that the effect of all independent variables on the dependent variable is 50.5% while the rest is explained by other variables. The results of the data analysis technique using multiple linear regression obtained a value (constant) of 0.791, the value of the coefficient of X1 0.548, the value of the coefficient of X2 was 0.456, the value of the coefficient of X3 was 0.316. The conclusion from the test results of each hypothesis shows that sales promotion has a significant effect on purchasing decisions, advertising has a significant effect on purchasing decisions, personal selling has a significant effect on purchasing decisions and sales promotion, advertising and personal selling have a significant effect simultaneously on purchasing decisions at PT. Great Mataram Surakarta Branch.